Perlindungan Hukum terhadap Waitress di Cafe Katulebo Berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Ida Bagus Alit Segara Gita; Nella Hasibuan Oleary; I Putu Gede Seputra (Warmadewa Press, 2020)
Waitress is usually tasked with pouring the drink that visitors ordered into a glass and accompanying visitors to sing while in the cafe. In labor law legal protection is provided in the form of legal protection in the field of job security where both in a relatively short or long time will be safe and there is a guarantee of safety for workers. In the case of liability to workers in the event of a work accident while carrying out their obligations at work the employer will bear the burden Arising materially by providingreimbursement for costs incurred due to work accidents based on the description the author gets the title Legal Protection Against Waitress at Katulebo Cafe Based on the Law Law Number 13 of 2003 concerning Employment. The aims of this study is to find out the legal protection provided by Katulebo cafe to waitresses according to Law No. 13 of 2003 concerning Employment and to find out the responsibility of Katulebo cafe for waitresses in work accidents. In practice the implementation of legal protection provided by the cafe to the waitress is only through a written agreement containing the regulations and what rights are obtained by the waitress. The form of responsibility given by the cafe to the waitress only provides a first-aid kit and compensation when work accidents occur. The writing method used is empirical legal research.